An 88-kilodalton antigen secreted by Aspergillus fumigatus. - Kobayashi, H (1993)
An 88-kDa component secreted in vitro by Aspergillus fumigatus has been purified by sequential chromatographic procedures. The molecule is a glycoprotein with an N-linked sugar moiety composed of mannose glucose, and galactose (16:10:1). It is recognized by antibodies from patients with aspergilloma and has potential for the immunodiagnosis of aspergilloma. The antigenicity is associated with the polypeptide part of the molecule (79 kDa).